The Effectiveness Of Learning During The Covid-19 Pandemic : Case Study At Stain Teungku Dirundeng Meulaboh - Marlina, Cut Nyak; Saputra, Rahmat; Rohana, Sy (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2023)
This study aimed to find out and describe the learning effectiveness during the Covid-19 pandemic at Tarbiyah and Teacher Training Department, State Islamic Institue (STAIN) Teungku Dirundeng, Meulaboh, along with its obstacles and solutions. This study employed the descriptive qualitative research method and was also categorized as field research. The subject of this study was limited to the learning process experienced by students in the sixth semester at the Islamic Education study program, Tarbiyah and Teacher Training Department, STAIN Teungku Dirundeng Meulaboh. The data-collecting techniques used in this study were observation, interview and documentation. The findings revealed that the learning process during the Covid-19 pandemic was executed in two ways: online and offline learning. Offline learning was viewed as more effective than online learning because offline learning allowed students to interact live with the lecturers and other students despite the health protocol application. On the other hand, online learning caused some obstacles, one of them was the unstable internet connection. There were some reasonably solutive solutions to this issue which as the reliable internet connection reaching out to the remote areas.